Magnetic Reversal in Wiegand Wires Evaluated by First-Order Reversal Curves - Yang, Chao (Materials (Basel), 2021)
The magnetic structure of Wiegand wires cannot be evaluated using conventional magnetization hysteresis curves. We analyzed the magnetization reversal of a Wiegand wire by measuring the first-order reversal curves (FORCs). A FeCoV Wiegand wire with a magnetically soft outer layer and a hard magnetic core was used in this study. The magnetization reversal of the soft and hard regions in the wire was identified in the FORC diagrams. The magnetization reversal of the dominantly irreversible process of the soft layer and the magnetic intermediate region between the soft and hard regions was clarified.